PERAN PERCEIVED VALUE, KEPERCAYAAN, DAN KEPUASAN PELANGGAN PADA LOYALITAS PELANGGAN PENGGUNA JASA EKSPEDISI “ANTERAJA” DI YOGYAKARTA - Wayan Sutame; Audita Nuvriasari (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to analyze the effect of Perceived Value, Trust, and Customer Satisfaction on Customer Loyalty of Anteraja expedition services in Yogyakarta. The sample in this study were 100 respondents who had used Anteraja's shipping services. The data collection technique used was a survey method with the research instrument used was a questionnaire. Instrument test results stated that the data in this study proved valid and reliable. In the Classical Assumption Test stated in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Perceived Value has a positive and significant effect on Customer Loyalty on Anteraja expedition services in Yogyakarta, (2) Trust has a positive and significant effect on Customer Loyalty on Anteraja expedition services in Yogyakarta, (3) Customer Satisfaction has a positive effect and significant to Customer Loyalty on Anteraja expedition services in Yogyakarta. These results have implications for supporting previous literature studies which state that customer loyalty is influenced by perceived value, trust and customer satisfaction. The findings of this study have implications for Anteraja shipping company in Yogyakarta in studying the level of customer loyalty and this research is expected to be a reference for companies in designing marketing strategies to increase customer loyalty.